2000
DOI: 10.1021/ic991441q
|View full text |Cite
|
Sign up to set email alerts
|

The Cubane-Type Mo2Ir2S4 Cluster Containing an Organohydrazido(2−) Ligand on the Mo Site

Abstract: Metal-sulfur cubane-type clusters have been attracting significant attention owing to their unique structures and properties. 1 Recent X-ray crystallographic studies on nitrogenase have revealed the structure of the FeMo cofactor cluster, which consists of two incomplete cubane-type units connected by three bridging sulfides {(MoFe 3 S 3 )(µ-S) 3 (Fe 4 S 3 )}. 2 This has spurred on particularly the syntheses of the cuboidal clusters relevant to this active site core, including those with {(MoFe 3 S 4 )(µ-S)(Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Our recent studies toward this direction have revealed that hydrosulfido-bridged dinuclear complexes such as [Cp*MCl-(µ-SH) 2 MCp*Cl] (M ) Ru, Rh, Ir; Cp* ) η 5 -C 5 Me 5 ) and [Cp 2 Ti(µ-SH) 2 RuCp*Cl] (Cp ) η 5 -C 5 H 5 ) serve as versatile precursors for preparing the homo-and heterobimetallic cubane-type clusters such as [(Cp*M) 4 (µ 3 -S) 4 ] (M ) Ru, 7 Rh, Ir 8 ), [(CpTi) 2 (Cp*Ru) 2 (µ 3 -S) 4 ], 9 and [CpTi(Cp*Ru) 3 -(µ 3 -S) 4 ] 10 through a dehydrochlorination-dimerization process (Scheme 1). In addition, it has also been found that the Ir-Mo cluster [(Cp*Ir) 2 {Mo(O)Cl 2 }{MoCl 2 (DMF)}(µ 3 -S) 4 ] can be obtained from [Cp*IrCl(µ-SH) 2 IrCp*Cl] and [MoO-(DMF) 3 (µ-S) 2 MoO(DMF) 3 ] 2+ through condensation and concomitant dehydration, 11 which is also shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies toward this direction have revealed that hydrosulfido-bridged dinuclear complexes such as [Cp*MCl-(µ-SH) 2 MCp*Cl] (M ) Ru, Rh, Ir; Cp* ) η 5 -C 5 Me 5 ) and [Cp 2 Ti(µ-SH) 2 RuCp*Cl] (Cp ) η 5 -C 5 H 5 ) serve as versatile precursors for preparing the homo-and heterobimetallic cubane-type clusters such as [(Cp*M) 4 (µ 3 -S) 4 ] (M ) Ru, 7 Rh, Ir 8 ), [(CpTi) 2 (Cp*Ru) 2 (µ 3 -S) 4 ], 9 and [CpTi(Cp*Ru) 3 -(µ 3 -S) 4 ] 10 through a dehydrochlorination-dimerization process (Scheme 1). In addition, it has also been found that the Ir-Mo cluster [(Cp*Ir) 2 {Mo(O)Cl 2 }{MoCl 2 (DMF)}(µ 3 -S) 4 ] can be obtained from [Cp*IrCl(µ-SH) 2 IrCp*Cl] and [MoO-(DMF) 3 (µ-S) 2 MoO(DMF) 3 ] 2+ through condensation and concomitant dehydration, 11 which is also shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…The action of NaBH 4 or LiBH 4 to ( n -Bu 4 N) 2 [ 2 ] solutions in THF was checked by ESI-MS, and no reaction was detected. Also, the reaction of this [ 2 ] 2- complex with hydrazines, NH 2 NH 2 or PhMeNNH 2 , did not show the formation of the corresponding condensation product, as observed in related oxo-molybdenum or tungsten complexes. Like compound ( n -Bu 4 N) 2 [ 2 ], the complexes ( n -Bu 4 N) 2 [ 3 − 6 ] do not react with sodium and lithium borohydride, NH 2 NH 2 , and PhMeNNH 2 . ESI-MS monitoring of the reaction between ( n -Bu 4 N) 2 [ 1 ] and sulfur showed the presence of an intact ( n -Bu 4 N) 2 [ 1 ] together with the formation of small amounts of the [Mo 3 S 7 (dmit) 3 ] 2- starting precursor.…”
Section: Resultsmentioning
confidence: 93%
“…10 In connection with this, our group has previously reported the catalytic N-N bond cleavage of hydrazine on thiolato-bridged diruthenium complexes, 11 as well as the synthesis of Mo 2 Ir 2 S 4 cubane-type sulfido clusters having dialkylhydrazido(2Ϫ) ligands. 12 As an extension of these studies, we have investigated the reactivities of the thiairidacycle complexes 1 toward hydrazines. When 1 was reacted with 1 equivalent of anhydrous hydrazine, the bridging mono(hydrazine) complexes…”
Section: Reaction Of 1 With Hydrazinesmentioning
confidence: 99%